2017
DOI: 10.1007/s10689-017-0015-9
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Lynch syndrome in young Saudi colorectal cancer patients using microsatellite instability testing and next generation sequencing

Abstract: Individuals with Lynch syndrome (LS) have germline variants in DNA mismatch repair (MMR) genes that confer a greatly increased risk of colorectal cancer (CRC), often at a young age. Identification of these individuals has been shown to increase their survival through improved surveillance. We previously identified 33 high risk cases for LS in the Saudi population by screening for microsatellite instability (MSI) in the tumor DNA of 284 young CRC patients. The aim of the present study was to identify MMR gene v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Out of the overall seven publications reporting different forms of risk factors ( Table 1 ; Figure 7 ), six studies reported genetic polymorphism as the possible risk factors. The adjusted OR (95%CI) ranged from 1.00 (0.50–2.00) to 1.00 (0.50–2.30) [11] , [49] – [53] . Two studies have attributed family history as a possible risk for CRC, with OR (95%CI) ranged from 1.00 (0.50–2.3) to 2.8 (2.00–4.1) [8] , [11] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of the overall seven publications reporting different forms of risk factors ( Table 1 ; Figure 7 ), six studies reported genetic polymorphism as the possible risk factors. The adjusted OR (95%CI) ranged from 1.00 (0.50–2.00) to 1.00 (0.50–2.30) [11] , [49] – [53] . Two studies have attributed family history as a possible risk for CRC, with OR (95%CI) ranged from 1.00 (0.50–2.3) to 2.8 (2.00–4.1) [8] , [11] .…”
Section: Resultsmentioning
confidence: 99%
“…The adjusted OR (95%CI) ranged from 1.00 (0.50–2.00) to 1.00 (0.50–2.30) [11] , [49] – [53] . Two studies have attributed family history as a possible risk for CRC, with OR (95%CI) ranged from 1.00 (0.50–2.3) to 2.8 (2.00–4.1) [8] , [11] . Only one study has highlighted ulcerative colitis and fatty diet as possible risk factors for CRC with OR (95%CI) of 2.8 (2.0–2.4) [8] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we found 3 variants that had large deletion (33%; 3/9). Alqahtani et al (21) carried out molecular analysis of MLH1, MSH2, MSH6 and PMS2 genes by NGS and MLPA in 13 of 33 Saudi patients with CRC <60 years at diagnosis. Nine variants were found (4 in MLH1 and 5 in MSH2) as pathogenic or likely pathogenic in 9 of the 13 patients (69%).…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors such as excess weight, sedentary lifestyle, diet rich in processed food, smoking, inflammatory bowel disease were found to contribute to 60-65% of CRC for both genders. Family history, due to the high rate of consanguineous marriage, and genetic syndrome (familial adenomatous polyposis or Lynch syndrome) account for 25-30% and 5%, respectively [27][28][29] . Polymorphisms of the ADIPOQ 30 , XRCC1, RETN 31 , and vitamin D receptor VDR 32 due to low vitamin D intake, have also been associated with increased risk CRC among Saudi older population.…”
Section: Crc Incidence and Mortality In Saudi Arabiamentioning
confidence: 99%